REACTION RATE LEARNING PROFILE TO IDENTIFY STUDENT CRITICAL THINKING SKILLS - Eni Purwanti (Chemistry Education Study Program Sriwijaya University, 2020)
This study aims to identify students' critical thinking skills that arise in the learning process commonly used by chemistry teachers on the topic of reaction rates. This research was conducted at one of the High Schools (SMA) in the City of Bandung, West Java Province. The research subjects were students of class XI MIPA. The method used in this research is descriptive qualitative research method with a case study approach. Description of students' critical thinking during the learning process was analyzed using TBLA (Transcript Based Lesson Analysis), namely audio and video transcript of the learning process. The results showed that students' critical thinking skills that appear in the learning process on the topic of reaction rate are based on 12 indicators of critical thinking skills, namely 3 indicators of critical thinking skills that emerge. Indicators that appear are answering questions, defining terms, and interacting with otherKeywords: critical thinking skills, learning, reaction rate, TBLA.